Penerapan Pendidikan Karakter melalui Model Pembelajaran Explicit Instruction dalam Mata Pelajaran Akidah Akhlak pada Peserta Didik Kelas XI di MA NU Wahid Hasyim Salafiyah Jekulo Kudus - Nuria Amrina Rosyada; Mukh Nursikin; Mohtarom Mohtarom (Departement of Mathematics Education, 2023)
This research is intended to answer the following problems: 1) How is the application of character education through the explicit instruction learning model in the subject of moral principles. 2) What are the supporting and inhibiting factors for the application of character education through the explicit instruction learning model in the subject of moral principles. 3) What are the advantages and disadvantages of the explicit instruction learning model in the subject of moral ethics. This research uses a type of field research research, namely field research conducted in madrasas. While the research approach that researchers use is a qualitative approach. Data collection techniques through observation, interviews and documentation. The source of the research is obtained through two different data, namely primary data and secondary data. In this thesis the author uses the theory of Miles and Huberman models to analyze data, namely through data reduction, data display, and data verification. The results of the research are as follows: 1) The explicit instruction learning model is applied on an ongoing basis to students in the Aqeedah Akhlak subject by demonstrating it continuously so that students can realize the values ​​of character education that must be achieved. 2) The application of character education through the explicit instruction learning model is supported by the cohesiveness of the teacher in providing motivation and educating, and supporting activities outside of teaching and learning activities (habituation and extracurricular activities), but is hampered by disturbances of loss of concentration which often occurs in some students. 3) The advantages of the explicit instruction learning model occur in teachers who have time flexibility in conveying material or experiences that can build the noble character of students, but have the disadvantage that teachers are really required to master the material, be active and extra active, so that they can master the class well. maximum.